Triathlete training and injury analysis - Vleck, V. (VDM Verlag Dr. Müller, 2010)
Triathlon which involves sequential swimming, cycling, and running- made its Olympic debut as the opening event of the Sydney 2000 Games, only 19 years after first being recognised by the I.O.C. It is both the fastest ever sport to achieve Olympic status and one of the fastest growing sports in the world. Despite its increasingly higher participation rates, minimal research is yet available regarding the potential risks for maladaptation to the cross-training that is involved in this exciting multi-sport. This book presents the results of the most comprehensive surveys yet available of training, injury and illness in National Squad triathletes. The work also sheds light on how the athlete may use his or her training diary to optimise his or her performance, through presentation of the results of a longitudinal prospective research study into the extent to which said training diary may be used to predict performance decrement, injury and or illness. As such, this doctoral thesis is both a thorough review and reference for researchers in the fields of injury epidemiology, sports science and sports medicine; and a valuable guide for multi-sport coaches and athletes.